Evaluation of the efficacy of intravenous ondansetron in comparison to ondansetron with dexamethasone for prevention of spinal anesthesia-induced hypotension in patients posted for infraumbilical surgeries – A prospective randomized double-blind study - Ananya Nanda; Supraja Ponduru; Vandana Patilbuwa Pakhare; R. Gopinath; Vamshidhar Malipeddi; Vyshnavi Renganathan (The Indian Anaesthetists' Forum)
Background and Aims: Spinal anesthesia is the preferred technique for infraumbilical surgeries. However, its association with complications such as hypotension (33%–80%) and bradycardia (13%) mandates caution in the perioperative period. This study aimed to compare the efficacy of ondansetron versus ondansetron with dexamethasone in preventing spinal anesthesia-induced hypotension and bradycardia in patients scheduled for non-obstetric infraumbilical surgeries. The time to rescue analgesia, time to two-segment regression, QTc interval changes, and blood glucose levels were examined as secondary objectives. Materials and Methods: In this prospective, double-blind, randomized study, 140 patients of the American Society of Anesthesiologists grades I and II, belonging to both sexes, undergoing infraumblical surgeries, were allocated to Group O (ondansetron n = 70) and Group OD (ondansetron and dexamethasone n = 70). After spinal anesthesia, patients’ hemodynamic parameters, including heart rate (HR); systolic, diastolic, and mean blood pressure; and SPO2, were noted every 3 min till 15 min and then every 5 min till 60 min or the end of surgery. Continuous measurements were presented as mean ± standard deviation, and categorical measurements were presented as numbers (%). The Student’s t-test was used to determine the significance of the study parameters on a continuous scale between the two groups. Results: HR, mean arterial pressure, and the requirement for mephentermine and atropine injections were comparable between the two groups. Rescue analgesic requirement was earlier in Group O, at 127.33 ± 37.229 min versus 219.58 ± 73.9 min in Group OD, indicating prolonged postoperative analgesic action (P ≤ 0.001). Higher blood glucose levels were observed 4 h after spinal anesthesia in Group OD (122 ± 25.43 mg/dL) than in Group O (108.13 ± 15.13 mg/dL), with a P < 0.001. Conclusion: Ondansetron, both as an individual molecule and combined with dexamethasone, effectively reduced the incidence of postspinal hypotension.